Penyuluhan Kesehatan Peduli Dan Waspada Terhadap Stroke Dengan Perilaku Cerdik Melalui Pendekatan Keluarga - Diana Dayaningsih; Erni Suprapti; Afrilia Frinda Parwati; Anggita Dwi Rahmawati; Annisa Amalia; Krido Aromanis Setia Pamungkas; Anugrah Tegar Laksono (BADAN PENERBIT STIEPARI PRESS, 2022)
Stroke is the number one cause of disability and the number three cause of death in the world after heart disease and cancer in both developed and developing countries. The burden due to stroke is mainly caused by disability (public health problem) which also creates a high cost burden for both sufferers, families, society and the state. In Indonesia, according to Riskesdas in 2017, stroke is also the highest cause of death in all age groups with a proportion of 15.4%, while in the 55 - 64 year age group it reaches 26.8% in both urban and rural areas and the youngest stroke cases are found in the 18 - 24 years old. The prevalence of stroke in Indonesia is 8.3 per 1000 population and those diagnosed by health workers are 6 per 1000 population. One promotive effort to control stroke is to provide health education through a family approach, inviting families to be more concerned and alert about stroke. Community Service Stikes Kesdam IV/Diponegoro Semarang is a form of one part of the Tri Dharma of Higher Education which seeks to provide benefits to public health through activities, especially in controlling stroke in the community. This Community Service takes the title